Persons of a Common Destiny Become Brothers: Documenting Narratives of the Second World War in Kidapawan - David, Karlo Antonio G. (Silliman Journal, 2022)
The present study sought to demystify the historiography of Kidapawan City, Cotabato Province, during the Second World War. It gathered surviving oral accounts of the War from some of the city’s oldest residents and families, recording them before they are lost to posterity. Together with information gathered from both local archival text and published references, these narrative accounts were then presented to tell a general picture of Kidapawan and its people during the War, from occupation to liberation. Some sections were dedicated to incidents of note: tribal resistance and the Kollut poisonings in Maliri and Kamasi, the kidnapping of Juan Sibug, the assassination of Eliseo Dayao Sr. the escape of Lorenzo Saniel from death, the forced leadership and symbolic incarceration of the hostage-mayor Filomeno Blanco, the torture of Patadon Tungao, and the romance and tragedy of Hayao Nakamura. In particular, the last incident is important to Kidapawan history, as Nakamura’s love affair and subsequent marriage with his secretary, Rosalina Madrid, led to a general “mellowing” of Japanese treatment to locals in Kidapawan. Many of these incidents and accounts see print for the first time with this study, and it is hoped more attention is given to them now that they have been recorded.